Code of practice for the safe use of lasers in schools (1995) (Radiation health series, 1995)
This code specifies administration requirements, procedures and equipment requirements considered necessary to eliminate potentially dangerous levels of ocular exposure and to ensure the safety of all persons where lasers are used for teaching purposes in schools.